Biomarkers of proliferation, survival, and migration of human breast tumor cells: future perspectives - Labovsky, Vivian (2019)
Despite recent major advance in the understanding of the mechanisms of breast cancer (BC) progression and in the development of novel therapeutic modalities, BC remains the second leading cause of mortality among women. Mortality is almost invariably due to metastasis. The different histological subtypes of BC and molecular maker expression (ER, PR and HER2) have strong prognostic and predictive values but are not enough to prevent that BC patients (BCP) develop a relapse and metastasis. So the aim of this work was the simultaneous evaluation of the expression of biomarkers related to BC progression and metastasis (OPG, TRAIL, TRAIL receptores (R) [R1, R2, R3 y R4], RANKL, RANK (RANKL-R), SDF-1, CXCR-4 (SDF-1-R), IL-6, IL-6-R, MCSF and M-CSF-R in BC cells together with the study of classic prognostic parameters (age, ER, PR, HER2, tumor size and histological grade) in BCP. Regarding the expression of these biomarkers in BC cells, the results are contradictory.